Desenvolvimento e caracterização de torradas tipo canapé elaboradas com carne de Tilápia-do-Nilo (Oreochromis niloticus) - Moreira, Dayvison Mendes (2023)
In order to stimulate or increase the consumption of fish, it is necessary to produce new products that meet the demands of the market, in addition to presenting functional proposals for the health of the consumer. Being likewise, the objective is to carry out a survey on the insertion of fish in baked products, through a bibliographic review of alternatives for the increase of fish in food through new products, addressing a topic relevant to the fish industry. This survey of information was the subject of the first review article of this dissertation. The second, experimental, article deals with the development of canapé-type toasts with the addition of nile-tilapia (Oreochromis niloticus) meat and evaluation of its microbiological, sensory, physicochemical and centesimal composition properties. From the results, the developed toasts were found in satisfactory hygienic conditions. In the sensory tests, the attributes will present notes in the oil pack at the maximum substitution of tilapia meat insertion, except for the texture of the product. For the purchase intention, the toasts with 30% tilápia meat were satisfactory for the consumers. In all the formulations there was a significant increase in two constituents in the percentage composition, except for tapes. In this way, it is recommended to add até 30% of tilápia meat to the formulations of toasts. There have been studies on the insertion of fish in bakery products, therefore there are still no reports on the development of roasts, therefore, new investigations are recommended in order to corroborate the information present in this study.